Faktor Penyebab Masyarakat Waiburak Tidak Mengurus Sertifikat Tanah Di Desa Waiburak Kecamatan Adonara Timur - Muda, Inna Maria Meylliani Boy; Usman, Siti R; Dinata, Husni Kusuma (Law Faculty, Nusa Cendana University, 2024)
According to the Agrarian Constitution and Leverage Regulation Number 24 of 1997, there are still many people, especially in Waiburak Village, who have taken their land certificates. This research is an empirical legal research. The factors that cause the Waiburak people to not care about land certificates are limited costs, problematic land, and also the lack of public awareness of the importance of land certificates. If these factors can be well minimized, then this ensures the validity of the ownership, and prevents disputes. (2) Because the law of the waiburak community does not take care of land certificates, legal uncertainty, difficulties in buying and selling transactions. The factors that cause the Waiburak community not to take care of land certificates are limited costs, land that is still problematic, lack of knowledge and public awareness about the importance of certificates. (2) Because the law of the Waiburak community does not take care of land certificates, legal uncertainty, difficulties in buying and selling transactions. The author's suggestion is that the government is expected to be more active in conducting intensive socialization related to the importance of land certificates as proof of legality, and to the community, to be more active in participating in socialization activities in order to get a better understanding of the procedures and importance of land certificates and the benefits of managing land certificates.